Establishing an Entrepreneurial Environment in Indonesia: Impact of CEO Social Capital, Marketing, and Financial Capabilities on the Performance and Sustainability of MSMEs - Susiati, Devi; Nurlia, Nurlia; Utami, Eva Yuniarti; Destiana, Rina (International Journal of Business, Law, and Education, 2024)
This study investigates the complex dynamics of creating an entrepreneurial ecosystem in Indonesia by examining the influence of CEO social capital, marketing capability, and financial capability on business performance. It also explores business performance implications for the sustainable business practices of MSMEs (Micro, Small, and Medium Enterprises) and the broader entrepreneurial ecosystem. A quantitative approach was used, incorporating quantitative data collected through offline and online surveys of 504 samples. Structural Equation Modeling - Partial Least Squares (SEM-PLS) 4 was used for data analysis. This study supported the hypothesis that CEO social capital, marketing, and financial capability significantly influence business performance. In addition, strong evidence was found for a positive relationship between business performance and sustainable business practices and the influence of sustainable business practices on the entrepreneurial ecosystem. This study underscores the multifaceted nature of entrepreneurship in Indonesia, where CEO social capital, effective marketing strategies, financial stability, and sustainable business practices are interconnected elements that contribute to firm success and the overall vitality of the entrepreneurial ecosystem. These findings have implications for policymakers, entrepreneurs, and stakeholders who want to encourage entrepreneurship, support MSMEs, and strengthen Indonesia's entrepreneurial ecosystem for sustainable economic growth and development.